Development of novel geopolymeric foam composites coated with polylactic acid to remove heavy metals from contaminated water. (June 2022) - Ramos, Flávio James Humberto Tommasini Vieira; Marques, Maria de Fátima Vieira; Rodrigues, João Gabriel Passos; Aguiar, Vinícius de Oliveira; da Luz, Fernanda Santos; de Azevedo, Afonso Rangel Garcez; Monteiro, Sergio Neves
Abstract: As an alternative for ordinary Portland cement, geopolymers are cost effective materials that can be prepared with relatively low energy consumption and substantial reduction of CO2 emissions. In the present study the characteristics of novel hybrid composite of geopolymer foam (GPF)/polylactic acid (PLA) and their efficiency in removing copper(II) and zinc(II) to treat high volumes of polluted water are investigated. Contrary to the conventional methods for removing heavy metals, the newly developed composites are ecological, low-cost, easily available, and economically viable alternatives providing good physical-chemical stability, ion-exchange properties, and a porous structure. Based on the sustainable advantage to produce geopolymers from recycled materials, GPFs were obtained from blast furnace slag (BFS) by reacting 20 ml of an 8 M alkaline solution of sodium metasilicate (Na2 SiO3 ) with BFS particles and later addition of hydrogen peroxide. GPFs were produced with a stoichiometry of 1.4 and 1.6 g/L between BFS/alkali solution with a 1.6 ml solution of hydrogen peroxide 50% to develop porosity into the materials. Finally, the GPFs were coated with PLA. Specimens of GPF/PLA composites were characterized by X-ray fluorescence spectroscopy, Fourier transformed infrared spectroscopy, thermogravimetric analysis, dynamic mechanical analysis, and field emission gun scanning electron microscopy. Adsorption analysis of Cu(II) and Zn(II), as well as ion-exchanges from aqueous solution through the composite with 1.4 and 1.6 stoichiometry, were performed using deionized water containing 0.80% Cu(II) or Zn(II). The test resulted in high performance for retaining Cu(II) and Zn(II). Under CO2 pressure at 50 bar, the gas permeation tests confirmed porous formations into the geopolymer foams coated with molten PLA.